2011
DOI: 10.1039/c1fd00040c
|View full text |Cite
|
Sign up to set email alerts
|

Coherent control of vibrational transitions: Discriminating molecules in mixtures

Abstract: Identifying complex molecules often entails detection of multiple vibrational resonances, especially in the case of mixtures. Phase shaping of broadband pump and probe pulses allows for the coherent superposition of several resonances, such that specific molecules can be detected directly and with high selectivity. Our particular implementation of coherent anti-Stokes Raman scattering (CARS) spectroscopy and imaging employs broadband pump and probe fields in combination with a narrowband Stokes field. We descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The last two decades have seen a significant expansion of the boundaries of quantum optimal control experiments (OCEs) due to technological advances in experimental resources, especially femtosecond lasers and pulse-shaping capabilities [1][2][3][4][5][6][7][8][9]. OCEs have been successfully performed for a wide range of goals, including the control of molecular vibrational [10][11][12][13][14][15][16][17] and electronic states [18][19][20][21][22][23][24][25][26], the generation and coherent manipulation of X-rays [27][28][29][30][31], the control of decoherence processes [32,33], the selective cleavage and formation of chemical bonds [34][35][36][37][38][39][40], the manipulation of energy flow in macromolecular complexes [41][42][43][44], and the control of photoisomerization reactions [45]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The last two decades have seen a significant expansion of the boundaries of quantum optimal control experiments (OCEs) due to technological advances in experimental resources, especially femtosecond lasers and pulse-shaping capabilities [1][2][3][4][5][6][7][8][9]. OCEs have been successfully performed for a wide range of goals, including the control of molecular vibrational [10][11][12][13][14][15][16][17] and electronic states [18][19][20][21][22][23][24][25][26], the generation and coherent manipulation of X-rays [27][28][29][30][31], the control of decoherence processes [32,33], the selective cleavage and formation of chemical bonds [34][35][36][37][38][39][40], the manipulation of energy flow in macromolecular complexes [41][42][43][44], and the control of photoisomerization reactions [45]…”
Section: Introductionmentioning
confidence: 99%
“…OCEs have been successfully performed for a wide range of goals, including the control of molecular vibrational [13][14][15][16][17][18][19][20] and electronic states [21][22][23][24][25][26][27][28][29], the generation and coherent manipulation of X-rays [30][31][32][33][34], the control of decoherence processes [35,36], the selective cleavage and formation of chemical bonds [37][38][39][40][41][42][43], the manipulation of energy flow in macromolecular complexes [44][45][46][47], and the control of photoisomerization reactions [48][49][50][51][52]. Optimal control theory (OCT) [7,9,[53][54][55][56] has provided insights into the coherent control of a variety of quantum phenomena, such as electron transfer …”
Section: Introductionmentioning
confidence: 99%
“…Closed-loop and open-loop methods were used to control the ratio between singlet and triplet states of zinc phthalocyanine, a model photosensitizer [185]. Using the shaped broadband pump and probe pulses in CARS, it was demonstrated that the evolutionary algorithm could find optimal pulse shapes, which will enhance the desired molecule's response and suppress the contribution from the other four molecules with overlapping resonance [186]. The method can be used in chemically-selective microscopy.…”
Section: Biosciencementioning
confidence: 99%
“…In the quest for label-free bioassays and label-free imaging techniques of biological tissues, coherent control [1,2] and in particular optimal dynamic discrimination (ODD) [3][4][5] recently emerged as an attractive novel method. The most relevant biological targets clearly consist of proteins, in which aromatic amino-acids (tryptophan, tyrosine, phenylalanine) provide sensitive fluorescing probes.…”
Section: Introductionmentioning
confidence: 99%